Histopathological Study of Whipple’s Pancreaticoduodenectomy Specimens at Tertiary Care Center - Chalise, Sanat; Hirachand, Suspana; Pradhan, Sailesh (Journal of Institute of Medicine Nepal, 2024)
Introduction Whipple’s pancreaticoduodenectomy has become a widely used resection procedure for pancreatic head, periampullary, ampullary, and biliary tumors. This study was conducted to analyze the histopathological features of these tumors in pancreaticoduodenectomy specimen. Methods A descriptive study was carried out in the Pathology Department of Kathmandu Medical College Teaching Hospital. Pancreaticoduodenectomy specimens received were assessed for tumor location, histopathologic categorization, grading, lymphovascular and perineural invasion, margin status, and lymph node status. AJCC TNM staging was done. Results Out of 41 Whipple’s pancreaticoduodenectomy cases, 35 (85.4%) were malignant and 6 (14.6%) were benign. The patients’ ages ranged from 30 to 84 years, with a mean age of 58.3 years and a male to female ratio of 1.2:1. Adenocarcinoma was the most common malignant lesion (73.2%; n=30) frequently found in the intra-ampullary and periampullary regions (31.4%; n=11). The intestinal type of adenocarcinoma was the most common (42.8%; n=15), followed by the pancreaticobiliary type (34.3%; n=12). Most tumors were moderately differentiated (74.3%; n=26). Perineural invasion was frequently seen in intra-ampullary and periampullary carcinoma (81.8%; n=9). Lymphovascular invasion was frequently seen in intra-ampullary and periampullary carcinoma (81.8%; n=9). Most tumors were in the T3 stage (42.9%; n=15), and overall nodal metastasis (N1 and N2) was seen in 57.1% (n=20). Conclusion Adenocarcinoma was the commonest diagsosis in pancreaticoduodenectomy specimens of the intra-ampullary and periampullary region. Malignant lesions were more frequent than benign lesion in our study.